Urinary angiotensinogen antedates the development of stage 3 CKD in patients with type 1 diabetes mellitus. Issue 19 (11th October 2019) - Ba Aqeel, Sheeba; Ye, Minghao; Wysocki, Jan; Sanchez, Alejandro; Khattab, Ahmed; Lores, Enrique; Rademaker, Alfred; Gao, Xiaoyu; Bebu, Ionut; Nelson, Robert G.; Molitch, Mark; Batlle, Daniel; et al.
Abstract: We examined if urinary angiotensinogen (uAOG), a marker of intrarenal renin‐angiotensin system activity, antedates stage 3 chronic kidney disease (CKD) using samples from participants in the Diabetes Control and Complications Trial (DCCT) and later in the Epidemiology of Diabetes Intervention and Complications (EDIC) trial. In a nested case–control design, cases were matched at the outcome visit (eGFR less than 60, 21‐59 mL/min per 1.73 m 2 ) on age, gender, and diabetes duration, with controls: eGFR (95, 75‐119, mL/min per 1.73 m 2 .) Additionally, in an exploratory analysis progressive renal decline (PRD), defined as eGFR loss >3.5 mL/min per 1.73m 2 /year, was evaluated using only data from EDIC because no progressions were observed during DCCT. At the EDIC visit, which antedated the GFR outcome visit by 2 years (range 1–7years) the median uAOG/creatinine was markedly higher in cases than in controls (13.9 vs. 3.8 ng/mg P = 0.003) whereas at the DCCT visit, which antedated the GFR outcome by 17 to 20 years it was not (2.75 vs. 3.16 ng/mg, respectively). The Odds Ratio for uAOG and CKD stage 3 development was significant after adjusting for eGFR, HbA1c, and systolic blood pressure 1.82 (1.00–3.29) but no longer significant when Albumin Excretion Ratio (AER) was included 1.21 (0.65–2.24).In the PRD analysis, uAOG/creatinine was sixfold higher in participants who experienced PRD than in those who did not (26 vs. 4.0 ng/mg, P = 0.003). The Odds Ratio for uAOG and PRD was significant after adjusting for eGFR, HbA1c, and systolic blood pressure 2.48 (1.46–4.22) but no longer significant when AER was included 1.32 (0.76–2.30). In people with type1 diabetes, a robust increase in uAOG antedates the development of stage 3 CKD but is not superior to AER in predicting this renal outcome. Increased uAOG moreover is associated with PRD, an index of progression to End Stage Kidney Disease (ESKD). Abstract : In people with type1 diabetes a robust increase in uAOG antedates the development of stage 3 CKD (eGFR < 60 ml/min/1.73m 2 ). In cases, unlike in controls with diabetes, Urinary AOG was not increased early on in the DCCT visit but increased markedly in the EDIC visit prior to the outcome visit in EDIC when eGFR fell below 60ml/min.